Microwave Dielectric Behaviour of Wet Soils - Behari, Jitendra (Remote Sensing and Digital Image Processing,, 2005)
Soil moisture plays an important role in the runoff process, and its evaluation can be used as a marker of flood risk or drought occurrence. The data is also required to validate the soil moisture component in a variety of soil types of hydrologic models before a possible flood event, and potentially improves the accuracy of their prediction. Keeping the above in view, enormous efforts have gone into measurement of soil moisture by in situ and remote sensing techniques using microwaves. The subject still remains an important point of investigation for it depends upon a number of parameters, for example, texture, topography and shows space and temporal variability. The advantages of both passive and active remote sensing techniques are discussed in detail. The book begins with the basics of soil physics and the soil moisture. Soil moisture measurement techniques presented are confined to microwave frequencies. A summary of theoretical models and a mix-up of experimental and theoretical details is included to offer a comparison. A special chapter is added on an upcoming technique of synthetic aperture radar. The book finally concludes with a summary of recent trends and techniques with a possible direction for future work. The book is primarily aimed to benefit postgraduates and researchers in the area of soil, agriculture physics and microwave remote sensing. The aim is to initiate beginners in the subject. The author will consider his efforts rewarded if it succeeds in such an endeavor.